2011
DOI: 10.1007/s11596-011-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in triptolide-induced apoptosis of renal tubular cells and renal injury in rats

Abstract: This study investigated the role of reactive oxygen species (ROS) in the pathogenesis of triptolide-induced renal injury in vivo. Rats were randomly divided into 4 groups (n=5 in each): triptolide group in which the rats were intraperitoneally injected with triptolide solution at a dose of 1 mg/kg of body weight on day 8; control group in which the rats received a single intraperitoneal injection of 0.9% physiological saline on day 8; vitamin C group in which the rats were pretreated with vitamin C by gavage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…In previously studies, DTH and improper dose of triptolide could cause significant kidney dysfunction [16], [43], [44]. Thus, as described above in this study, the down-regulation of sphingolipid levels might correlate with the exacerbation of kidney dysfunction.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…In previously studies, DTH and improper dose of triptolide could cause significant kidney dysfunction [16], [43], [44]. Thus, as described above in this study, the down-regulation of sphingolipid levels might correlate with the exacerbation of kidney dysfunction.…”
Section: Resultssupporting
confidence: 63%
“…Thus, both DTH induced by DNFB and treatment with triptolide have harmful effects on the kidney. Many previous studies have shown the deleterious effects of triptolide on kidney function; TWHF was toxic to rodent kidneys even at normal dosage levels [15], [16], [44][46]. These early studies reported that oxidative stress caused by triptolide is involved in drug-induced nephrotoxicity by reducing the activity of renal superoxide dismutase and glutathione peroxidase and increasing renal malondialdehyde content [16], [44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABT % Inhibition of CYP3A by ABT Cytotoxicity without ABT Cytotoxicity with ABT (Shu et al, 2009;Yang et al, 2011). In the current study, it was confirmed that TP did upregulate the antiapoptosis protein Bax and downregulate the proapoptotic protein Bcl-2 in SCRH.…”
Section: Groupsmentioning
confidence: 99%
“…However, TPL rapidly reaches C max (10 min), distributes in the other organs and excreted (t 1/2 , 38 min) via biliary, urinary and fecal routes after oral administration [ 5 ]. The toxic and side effects on liver and spleen were reported frequently [ 6 , 7 ]. Thus, TPL formulation with better patient compliance and controlled release required more studies in novel drug delivery routes, including transdermal delivery.…”
Section: Introductionmentioning
confidence: 99%